Good policies or good fortune: What drives the compression in emerging market spreads? - Philipp Maier; Garima Vasishtha (Bank of Canada, 2008)
Since 2002, spreads on emerging market sovereign debt have fallen to historical lows. Given the close links between sovereign spreads, capital flows to emerging markets, and economic growth, understanding the factors driving these spreads is very important. We address this issue in two stages. First, we use factor analysis to study the extent to which emerging market bond spreads are driven by global factors, as opposed to country-specific macroeconomic fundamentals. Using data on different U.S. asset classes, we identify a common factor, linked to global financial conditions. Second, we use this common factor in a panel estimation framework to analyze the degree to which the fall in spreads is driven by better macroeconomic policies. Our results show that the common factor is not responsible for the reduction in spreads. Instead, emerging markets have benefited considerably from better macroeconomic policies, including lower inflation and lower debt. Therefore, a reversal of the benign global conditions need not necessarily have a substantial negative impact on financing conditions for emerging markets.
Keywords: E43; F34; G12; G15; 330; Development economics; Financial stability; International topics; Auslandsverschuldung; Kapitalimport; Kosten; Volatilität; Wirtschaftspolitik; Wirtschaftswachstum; Kreditwürdigkeit; Aufstrebende Märkte